PENGINTEGRASIAN PENDIDIKAN LINGKUNGAN HIDUP MEMBENTUK KARAKTER PEDULI LINGKUNGAN DI SEKOLAH DASAR - Shanta Rezkita; Kristi Wardani (Universitas Sarjanawiyata Tamansiswa, 2018)
Abstract: This study aims to explore the strategy of integrating the environment in shaping the character of environmental care in the Bhayangkara Elementary School. This research is a qualitative descriptive research. Techniques of collecting data using interviews, observation, and documentation. Data analysis uses data collection, data reduction, data presentation, and conclusions. Validity checks data using source triangulation, technique, and time. The results showed that teachers in planning learning include habituation, exemplary and learning while doing. The steps taken by the teacher include: using learning media and environment as a place of learning. Teachers in conducting assessments focus more on affective judgments. Supporting factors such as the performance of teachers, principals and gardeners in guiding students and the existence of learning media that allows students to understand the value of environmental care. Inhibiting factors such as lack of learning time and family role in instilling environmental caring value.